Communicative tolerance and satisfaction with interpersonal relationships during young women’s gender socialization - Lovchynska, Tetyana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The paper covers theoretical and methodological analysis of gender socialization, reveals the peculiarities of the connection between communicative tolerance and satisfaction with interpersonal relationships during young women’s gender socialization, and presents empirical investigation of the identification of dominant connections between the communicative tolerance and satisfaction with interpersonal relationships.